Delphi assessment of occupational hazards in the wineries of Andalusia, in southern Spain. - Anaya-Aguilar, Rosa María; Suárez-Cebador, Manuel; Rubio-Romero, Juan Carlos; Galindo-Reyes, Fuensanta Carmen (Elsevier, 2018)
Risk assessment is essential to making informed decisions on occupational risk prevention. The health and safety conditions of workers can be improved by issuing voluntary certifications, such as ISO 45001. This is particularly important in sectors such as wineries. In 2017 these numbered 4093, representing 14% of the food and drink industry in Spain, of which 290 were in Andalusia. The incidence rate for 2017 in the industrial sector in Spain was 5.264 work accidents with sick leave for every 100,000 affiliated workers, making this the sector with the second highest number of work accidents after that of construction. The study aims to assess the risks in wineries in Andalucía, southern Spain, by analysing the opinions of a group of experts with experience in the sector. The Delphi method was used for this study and was carried out in conjunction with a panel of 11 experts. The results indicated that the most significant workplace risks were those occurring in the production facility, workshop or factory; in terms of occupation, those exposed to the greatest risk were machine operators; regarding the type of work, production, processing and storage posed the highest levels of risk; operating machinery was the physical activity with the highest risk; in the area of causes of accidents, the highest risk was of slipping, tripping and falling; and, finally, with regard to how an accident could occur, the highest level of risk was considered to be contact with electric current.
https://v2.sherpa.ac.uk/id/publication/13808
Keywords: Seguridad e higiene laboral; Accidentes de trabajo; Bodegas; Wine cellar; Risk assessment; Occupational accidents; Safety; Health